â€œGawaiâ€: Cultural Activities in the Shroud of Jangkang Bokidoh Dayak Tribe Traditional Architecture in Balai Sebut Village - Setyabudi, Irawan; Santoso, Dian Kartika; Albina, Katarina (University of Merdeka Malang, 2021)
Balai Sebut Village located in Perintis Hamlet, Sanggau Regency, which has indigenous people, namely Dayak Jangkang Bokidoh. Local wisdom in those areas still closely held, either tangible, such as traditional architectural forms, or intangible, such as traditional and cultural activities. This study discusses the visual form of the traditional house, the pattern of micro-space arrangement and traditional activities that use the â€œGawaiâ€ space. â€œGawaiâ€ is a religious ceremony as a sense of gratitude which involves the use of micro to macro spaces. The purpose of this research is to focus on the identification of house forms, settlement patterns, and cultural activities that using an architectural space as an effort to preserve traditional architecture which is precisely in Perintis Hamlet. The research method was carried out in a descriptive-qualitative manner with an ethnographic approach. Data collection was carried out through a focus group discussion. The results showed that the Dayak Jangkang Bokidoh tribe had architectural tangible and intangible values. Physical spaces that have architectural value will have meaning if there are activities that involve the space. In this case, seven kinds of traditions are still preserved in Balai Sebut village, namely in the form of â€œGawaiâ€, which are related to the presence of ancestors, gratitude for the harvest, birth, death, and marriage as cultural activities that must be preserved together with the traditional house. So, â€œGawaiâ€ can be said as a cultural activity that gives meaning to space in the traditional architecture of the Jangkang Bokidoh Dayak Tribe.Â DOI:Â https://doi.org/10.26905/lw.v13i1.4816